Lingvistična antropologija in etnolingvistika Linguistic Anthropology and Ethnolinguistics - Babič, Saša (Studia mythologica Slavica, 2011)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The article is a review of the development of linguistic anthropology and etholinguis tics. It examines connections and differences between them, and the differences between Moscow and Lublin tendencies. It also tries to state the methods of linguistic anthropology and the ethnolinguistic methods in Slovenia.